Orlicz strongly convergent sequences with some applications to fourier series and statistical convergence - Raj, Kuldip; Kilicman, Adem (Yildiz Technical University, 2018)
In the present work we introduce and study some strongly convergent sequence spaces of Orlicz functions using inﬁnite matrix over n-normed spaces. We study some algebraic and topological properties ofthese sequence spaces. A necessary and sufﬁcient condition for strongly convergent sequences is obtained. Finally, we study some applications of these sequences for Fourier series and statistical convergence.